1972
DOI: 10.1080/00288233.1972.10421250
|View full text |Cite
|
Sign up to set email alerts
|

Beef production from the dairy herd: calving performance of cows

Abstract: Data are reported on the calving performance of cows in beef production trials in three successive calvings of South Auckland herds. The main comparison of Friesian, Hereford, and Charolais sires over the Jersey cow is supplemented by information on the Friesian cow mated to these three sire breeds and on straightbred Jersey and straightbred Angus calvings.Overall, 81% of ca1vings were unobserved. Eight percent of all ca1vings, or 45% of observed calvings, were assisted. Jersey and Friesian cows required more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…An acceptably accurate assessment of the dystocia incidence associated with individual bulls, such as that provided for some bulls in the New Zealand Dairy Board's artificial breeding service, would be of distinct value to the dairy farmer faced with the choice of alternative bulls of the fame breed. Statistically significant variation between sires-within-breeds for birth weight and gestation length was also found previously (Everitt & Jury 1972), and the present heritability estimates are comparable for birth weight, but higher for gestation length, than reported by those autho,'s. Heritability of calving difficulty, subjectively assessed, appears low (Brinks et ai, 1973: Hansen 1975Tong et ai.…”
Section: 3contrasting
confidence: 50%
See 4 more Smart Citations
“…An acceptably accurate assessment of the dystocia incidence associated with individual bulls, such as that provided for some bulls in the New Zealand Dairy Board's artificial breeding service, would be of distinct value to the dairy farmer faced with the choice of alternative bulls of the fame breed. Statistically significant variation between sires-within-breeds for birth weight and gestation length was also found previously (Everitt & Jury 1972), and the present heritability estimates are comparable for birth weight, but higher for gestation length, than reported by those autho,'s. Heritability of calving difficulty, subjectively assessed, appears low (Brinks et ai, 1973: Hansen 1975Tong et ai.…”
Section: 3contrasting
confidence: 50%
“…This suggests that some farmers may have anticipated difficult calving for cows in-calf to some sire breeds and rendered assistance whether it was needed or not. There was no evidence of farmers anticipating calving difficulties in a previous study (Everitt & Jury 1972) which reported calving of F and J cows in-calf to C sires over three successive calving seasons.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations